Sound Sentiment: An Essay on the Musical Emotions. Including the Complete Text of the Corded Shell - Kivy, Peter 1934-2017 (Philadelphia, PA Temple University Press, 1989)
"Kivy's is a lucid and eminently readable account, interesting both historically and conceptually, of musical expressiveness--flexible in that it gives scope to both the contour and the convention models, the account becoming more convincing as one reads, as the theory is applied to more and more specific passages of music, and as one after another bit of irrelevancy or pseudo-mysticism is progressively shucked off." --John Hospers, Journal of Aesthetic Education "The Corded Shell, in its clarity, judiciousness, and breadth, will clearly take its place as a major work on musical expression. Those who seek to chart the murky waters of musical aesthetics are permanently in Kivy's debt." --Jerrold Levinson, Canadian Philosophical Review "Informed, lucid, and witty, Professor Kivy's argument brings enlightened solace to the musical amateur and tempers the harsh stance of the musical purist. A splendid contribution to the aesthetics of music." --Virginia Quarterly Review
Keywords: Music philosophy and esthetics